2013
DOI: 10.1002/pen.23463
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polypropylene/nanoclay composite fibers

Abstract: Melt spinning of nanoclay (NA)/polypropylene (PP) composites into textile fibers is studied. The synthetic NA Perkalite F100 is prone to be exfoliated in PP matrix. With the help of a maleic anhydride‐grafted low‐molecular‐weight PP as compatibilizer (Epolene E43), a highly exfoliated PP/NA composite was successfully prepared. However, the prepared PP/NA composite shows a poor spinnability because of the phase separation between Epolene E43 and PP matrix. The combination of two different groups of compatibiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Moreover, since the chemical composition can be precisely controlled, these materials can find applications where the chemical purity is required, for example in food, medical, and microelectronic industries . In general, LDH has a layered structure similar to silica clays, but the layers positively charged with an anionic interlayer gallery can be exchanged by bulk organic anions; when the interlayer distance is increased, polymer chains can intercalate into the gallery and thus nanocomposites with an intercalated and/or exfoliated morphology can be obtained …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, since the chemical composition can be precisely controlled, these materials can find applications where the chemical purity is required, for example in food, medical, and microelectronic industries . In general, LDH has a layered structure similar to silica clays, but the layers positively charged with an anionic interlayer gallery can be exchanged by bulk organic anions; when the interlayer distance is increased, polymer chains can intercalate into the gallery and thus nanocomposites with an intercalated and/or exfoliated morphology can be obtained …”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Recently many articles on synthetic layered double hydrotalcite (LDH) have been published. [26][27][28][29][30][31][32][33][34] LDH is a synthetic clay produced in a broad range of chemical compositions. Moreover, since the chemical composition can be precisely controlled, these materials can find applications where the chemical purity is required, for example in food, medical, and microelectronic industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fiber properties were found to be dependent on the polypropylene melt flow, ranging between 12 and 35 dg/min (230°C, 2.1 6kg), the nanoclay composition, and the spinning and drawing conditions. Recently, the preparation of polypropylene-nanoclay composite fibers starting from hydrotalcite has been described by Guo and Hagstrom [24]. The present work details the formulation of hydrotalcite/polyethylene composite and the production of melt spun fiber.…”
Section: Introductionmentioning
confidence: 95%
“…Take injection-moulded parts as an example: a very small amount of shish-kebabs can be in situ developed in the nal injectionmoulded parts, and moreover they are only located in an extremely thin layer close to the surface due to the intense shear and fast solidication therein. Due to the extraordinary mechanical properties, a wide range of inorganic llers including clay, [21][22][23][24] calcium carbonate, 25,26 carbon nanotubes, 27,28 etc., have been utilized to prepare reinforced composites. 20 To date, studies on semi-crystalline polymer-based (e.g., polyethylene and polypropylene) composites have indicated that reinforced llers are roughly classied into two categories: inorganic and organic ones.…”
Section: Introductionmentioning
confidence: 99%